Pulsed radiofrequency treatment of the lumbar dorsal root ganglion in patients with chronic lumbar radicular pain: a randomized, placebo-controlled pilot study - Shanthanna H; Chan P; McChesney J; Thabane L; Paul J (Journal of Pain Research, 2014)
Harsha Shanthanna,1 Philip Chan,1 James McChesney,1 Lehana Thabane,2 James Paul1 1Department of Anesthesia, 2Department of Clinical Epidemiology and Biostatistics, St Joseph's Hospital, McMaster University, Hamilton, ON, Canada Background: No proof of efficacy, in the form of a randomized controlled trial (RCT), exists to support pulsed radiofrequency (PRF) treatment of the dorsal root ganglion (DRG) for chronic lumbar radicular (CLR) pain. We determined the feasibility of a larger trial (primary objective), and also explored the efficacy of PRF in decreasing pain on a visual analog scale (VAS) and improving the Oswestry Disability Index. Methods: This was a single-center, placebo-controlled, triple-blinded RCT. Patients were randomized to a placebo group (needle placement) or a treatment group (PRF at 42°C for 120 seconds to the DRG). Patients were followed up for 3 months post procedure. Outcomes with regard to pain, Oswestry Disability Index score, and side effects were analyzed on an intention-to-treat basis. Results: Over 15 months, 350 potential patients were identified and 56 were assessed for eligibility. Fifteen of them did not meet the selection criteria. Of the 41 eligible patients, 32 (78%) were recruited. One patient opted out before intervention. Three patients were lost to follow-up at 3 months. Mean VAS differences were not significantly different at 4 weeks (-0.36, 95% confidence interval [CI], -2.29, 1.57) or at 3 months (-0.76, 95% CI, -3.14, 1.61). The difference in mean Oswestry Disability Index score was also not significantly different at 4 weeks (-2%, 95% CI, -14%, 10%) or 3 months (-7%, 95% CI, -21%, 6%). There were no major side effects. Six of 16 patients in the PRF group and three of 15 in the placebo group showed a >50% decrease in VAS score. Conclusion: The recruitment rate was partially successful. At 3 months, the relative success of PRF-DRG was small. A large-scale trial to establish efficacy is not practically feasible considering the small effect size, which would necessitate recruitment of a challengingly large number of participants over a number of years. Until clear parameters for application of PRF are established, clinicians will need to use their individual judgment regarding its clinical applicability, given the present evidence. Keywords: pulsed radiofrequency, radicular pain, dorsal root ganglion